Development of Make a Match Type of Learning Tools Assisted by Worldwall Applications on ASEAN Materials to Improve Critical Thinking Ability of Elementary School Students - Hendra Anang; Wahyu Sukartiningsih; Waspodo Tjipto Subroto (EduLine: Journal of Education and Learning Innovation, 2022)
Enforcement of online learning requires teachers to be able to use information technology to conduct online learning. It was found in online learning that some students were less enthusiastic about paying attention to the teacher's explanation, did not answer the teacher's questions, and were less active in expressing opinions. So, we need a learning innovation so that students feel comfortable and happy to learn and do not rule out the material that must be mastered by students with the Make a Match learning model assisted by the Worldwall application. The purpose of the study was to describe the effectiveness of the Make a Match cooperative model assisted by the Worldwall Application on ASEAN materials to improve critical thinking skills of elementary school students. The type of research used is a learning tool developed and made using the Make a Match Cooperative type which is supported by the Worldwall Application in ASEAN Materials at SDN Banjarsugihan II/117 Surabaya. The results of the responses of class VI B students to the Make a Match Type learning device with the help of Worldwall Applications with Cooperatives showed a positive response to improve students' critical thinking skills and provide a good understanding of the material being taught with a percentage of 89%. Teachers are also active in motivating and assisting students in providing reinforcement and responding to student work with the aim of making it easier for students to understand and solve problems regarding fractions so that they can be used as alternatives in learning ASEAN material. Keyword: Make a Match, Worldwall, ASEAN